Real estate investment - a financial and bibliometric analysis - Ichim, Cristinel; Grosu, Veronica; Cosmulese, Cristina Gabriela; Mihaila , Svetlana; Brinzaru, Simona Maria (Serbian Journal of Management, 2026)
The investigation of real estate risks, exuberance and housing bubbles have garnered a lot of attention, leading to significant implications on governments, industry and human beings. Their compliance with the competitive market economy has led to the identification of certain distinctive features and risks, such as the atomization of requests and offers, the piecing fluidity, the personalization of requests, and sales-focused production. Thus, much research has been conducted on the topic of real estate investment over the last two decades. However, discussing the impact of real estate investing in the context of radical cultural changes driven by overlapping crises, technological innovation pressures, and environmental concerns continues to lack systematic and in-depth bibliometric research. This paper aims to consolidate standard research on the bibliometric study of papers and articles published over the last 23 years, from 2000 to 2023. This paper aims to advance our understanding of this cross-cutting concern using a review of the bibliometric literature on the house price bubble thus providing both a quantitative and qualitative perspective on productivity related to this area of economic research. The results from 1,780 studies analyzed show evolving trends in the keywords financial investments, real estate investment, commerce, risk assessment and artificial intelligence. traditional commerce-related keywords and have increasingly begun to include elements of risk assessment and artificial intelligence, reflecting a continuous adaptation to new technological and economic challenges and opportunities. Future research may cover other databases for more comprehensive analysis
Keywords: real estate investments; bibliometric analysis; economic crisis; cultural shift; market trend